Notes on the genus Stichorkis (Orchidaceae, Malaxidinae) in Malesia: new combinations, synonyms and lectotypification - Naive, Mark Arcebal K. (Universidad de Costa Rica, 2019)
41 new combinations, two synonyms and three lectotypifications from the genus Stichorkis are proposed. This work aimed to solve taxonomic ambiguity and nomenclatural crisis for Malesian Stichorkis.